Efficacy of Diphenyleneiodonium Chloride (DPIC) Against Diverse Plant Pathogens. Issue 1 (2nd January 2019) - Jung, Boknam; Li, Taiying; Ji, Sungyeon; Lee, Jungkwan
Abstract: Many of the fungicides and antibiotics currently available against plant pathogens are of limited use due to the emergence of resistant strains. In this study, we examined the effects of diphenyleneiodonium chloride (DPIC), an inhibitor of the superoxide producing enzyme NADPH oxidase, against fungal and bacterial plant pathogens. We found that DPIC inhibits fungal spore germination and bacterial cell proliferation. In addition, we demonstrated the potent antibacterial activity of DPIC using rice heads infected with the bacterial pathogen Burkholderia glumae which causes bacterial panicle blight (BPB). We found that treatment with DPIC reduced BPB when applied during the initial flowering stage of the rice heads. These results suggest that DPIC could serve as a new and useful antimicrobial agent in agriculture.